PREVALÊNCIA DE CÁRIE EM CRIANÇAS DE 3 A 5 ANOS DE ESCOLAS PÚBLICAS EM PONTA GROSSA-PR, SEGUNDO DOIS CRITÉRIOS DIAGNÓSTICOS: ceo-d e ICDAS II - Cunha, Cinthia Maria Baggio de Luca da (2016)
This cross-sectional research evaluated the caries prevalence of pre-school children from public schools in Ponta Grossa (PR, BR), using dmf-t index (recommended by the World Health Organization) and ICDAS II (International Caries Detection and Assessment System). A probabilistic sample of 931 children (3-5 years old), from 18 public nursery schools, were examined by two calibrated researchers. The mean dmf-t was 1,8 ± 2,9, with a caries prevalence of 42,9%. Using the three cut-off points of ICDAS II (≥1, ≥3 e ≥4), the caries prevalence were 50,7%, 40,8% and 30,7%, respectively; and the amount was 2,32 ± 3,33. Five years-old children exhibited the highest caries prevalence, assessed with dmf-t index or ≥3 e ≥4 cut-off points of ICDAS II (≥3: p=0,032; ≥4: p=0,015). There were no differences among 3, 4 or 5 ages when considering children that showed only enamel white spots (p=0.106). The evaluation of carious lesion distribution in different tooth types according to ICDAS II system showed that lower molars and upper incisors were the most affected (p<0.001). Regarding dental arches, higher caries prevalence was found in upper arches (p<0.001). The dmf-t index also demonstrated a substantial difference between cavitated (82,45%) and restored teeth (17,55%). It’s concluded that both indexes assessed the caries experience of the sample in a similar manner, but the use of dmf-t index in epidemiological surveys may underestimate the caries prevalence since it doesn’t contemplate the early signs of the caries disease (enamel white spots). The caries prevalence enhanced when the cut-off point of the ICDAS II system was diminished. Both dmf-t index and ICDAS II system pointed to an expressive need of restorative treatment, however the use of ICDAS II system allows early intervention and the application of non-invasive procedures.